2012
DOI: 10.4104/pcrj.2011.00102
|View full text |Cite
|
Sign up to set email alerts
|

Beyond lung function in COPD management: effectiveness of LABA/LAMA combination therapy on patient-centred outcomes

Abstract: Bronchodilators are central to the management of chronic obstructive pulmonary disease (COPD). Clinical studies combining different classes of bronchodilators, in particular a long-acting muscarinic antagonist (LAMA) and a long-acting β2-agonist (LABA), have demonstrated greater improvements in lung function (forced expiratory volume in 1 second, FEV1) in patients with COPD than monotherapy. FEV1 has served as an important diagnostic measurement of COPD, and the majority of clinical studies of currently availa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
49
0
9

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 103 publications
(58 citation statements)
references
References 37 publications
0
49
0
9
Order By: Relevance
“…With a growing body of evidence demonstrating the benefits of dual bronchodilation over monotherapy in a number of clinical settings [4,[9][10][11][12]41], focus is now turning to the relative benefits of different bronchodilator combinations [14]. Indirect evidence from network meta-analyses indicate an efficacy gradient within the LAMA/LABA class with respect to lung function [14,15,23], and this study, the first head-to-head study of UMEC/VI and TIO/ OLO, confirmed the results of the indirect comparisons in both an all-comer and MN population [21].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…With a growing body of evidence demonstrating the benefits of dual bronchodilation over monotherapy in a number of clinical settings [4,[9][10][11][12]41], focus is now turning to the relative benefits of different bronchodilator combinations [14]. Indirect evidence from network meta-analyses indicate an efficacy gradient within the LAMA/LABA class with respect to lung function [14,15,23], and this study, the first head-to-head study of UMEC/VI and TIO/ OLO, confirmed the results of the indirect comparisons in both an all-comer and MN population [21].…”
Section: Discussionmentioning
confidence: 99%
“…A majority of patients who receive LAMA or LABA monotherapy continue to experience ongoing moderate-to-severe dyspnea, regardless of the level of lung function impairment [6], and this symptom persistence can be associated with poor health status, as well as a higher risk for moderate and severe exacerbations and augmented disease management costs [7,8]. There is now a large body of evidence to show that LAMA/LABA combinations consistently improve lung function, breathlessness and health status with no increased incidence of adverse events (AEs), compared with either LABA or LAMA alone [4,[9][10][11][12][13][14][15]. As such, LAMA/LABA combination therapy is recommended as initial therapy in most patients with persistent COPD symptoms [1].…”
Section: Introductionmentioning
confidence: 99%
“…In the last decade, multiple randomized controlled trials (RCTs) have reported that improvements in lung function and patient-reported outcomes (PROs) can be achieved with LAMA ? LABA combinations compared with the component monotherapies for patients with stable COPD, with no differences in safety [14][15][16][17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%
“…1,5,6 Achados reforçam a ideia de que broncodilatadores com mecanismos de ação diferentes podem melhorar a eficácia no manejo dos sintomas e diminuir o risco de eventos adversos comparados ao aumento de dose de um agente isolado. [7][8][9] Adicionalmente, evidências de estudos prospectivos tem demonstrado significante melhora na função pulmonar da combinação em dose fixa LABA/LAMA comparada aos seus monocomponentes ou a outro LAMA. [10][11][12] Recentemente, os LABAs de ação ultralonga (ultra-LABAs) com ação terapêutica de 24 horas foram lançados no mercado brasileiro.…”
Section: Introductionunclassified
“…17 Embora o VEF 1 seja rotineiramente utilizado para avaliar resposta bron-codilatadora, sabe-se que mudanças nesse parâmetro não tem sido suficientes para detectar respostas funcionais significativas a broncodilatadores, e, consequentemente, para avaliar impacto de um tratamento em um paciente com obstrução ao fluxo aéreo. 7,17,18 Nesse sentido, outros parâmetros espirométricos, a exemplo da CI, podem ser relevantes na avaliação da resposta broncodilatadora, sobretudo em pacientes sintomáticos. 19 Apesar da larga disponibilidade de LABAs e LAMAs, isolados ou em combinações em doses fixas, dados de ensaios clínicos de comparação direta de diferentes esquemas de terapias duplas são escassos.…”
Section: Introductionunclassified